Inflasi dan Cara Mengatasinya dalam Islam - Reni Mulyani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
Inflation is a monetary event that results in a decrease in the value of currency for certain goods. This incident causes disruption to the function of money, distorts prices, destroys output, undermines efficiency and productive investment, and causes social injustice. The method in writing this article is to use a literature study with a descriptive-analytic qualitative approach, namely research that is emphasized on tracing and analyzing. written sources and other reading material related to the theme discussed for further study and in-depth study. This research was conducted to examine inflation and how to overcome it in Islam. Inflation is a condition where there is an increase in prices in general and it takes place continuously. Inflation is also a state of continuous decline in the value of currency. In general, inflation is caused by: the large number of public demand for an item, an increase in production costs, and the very high circulation of money in society. Meanwhile, according to Al-Maqrizi Taqyudin in the Islamic economy inflation is caused by natural inflation (naturally) and human error inflation (by humans). According to its nature inflation is divided into creeping inflation, medium inflation (galloping inflation), high inflation (hyper). inflation). According to the cause of inflation, it is divided into Demand Pull Inflation and Cosh Push Inflation. According to the origin, inflation is divided into inflation originating from within the country and from abroad. Meanwhile, according to public expectations it is divided into Expected inflation and Unexpected inflation. In conventional economies the way to overcome inflation is by implementing monetary policy, fiscal policy, non-monetary / non-fiscal policies. Whereas in Islam inflation is overcome by printing low / minimal amounts of money, implementing the Dues Idle Fund strategy, and implementing fiscal policy.